Numerical solution of time fractional Schrödinger equation by using quadratic B-spline finite elements - Esen, Alaattin; Tasbozan, Orkun (Annales Mathematicae Silesianae, 2016)
In this article, quadratic B-spline Galerkin method has been employed to solve the time fractional order Schrödinger equation. Numerical solutions and error norms L2 and L∞ are presented in tables.